Design and synthesis of 3,4-seco-Lupane triterpene derivatives: targeting tumor angiogenesis and inducing apoptosis in triple-negative breast cancer - Gao, Chunyu; Teng, Hongbo; Zhang, Wenxin; Zhao, Yaru; Cui, Chunguo; Patrice, Zerbo; Wang, Liyan; Zhao, Yan (Frontiers in Chemistry, 2025)
BackgroundDue to the lack of effective treatment methods and targeted drugs, triple-negative breast cancer (TNBC) is not only difficult to treat clinically, but also has a poor prognosis for patients. This study aims to develop novel anti-TNBC drug candidates by designing 90 derivatives of 3,4-seco-lupane triterpene derivatives, a natural product of the genus Eleutherogenus.MethodsFirstly, 90 derivatives were synthesized and screened, and the compound I-27 showed excellent cytotoxicity (IC50=1.02 μM) for MDA-MB-231 cells for further activity verification. Then in vitro tests were carried out to detect the effects of the compound on the proliferation, migration, invasion and apoptosis of TNBC cells. With the help of transcriptomics, the mechanism of action was explored and verified. At the same time, its inhibitory effect on tumor volume and lung metastasis was verified through a mouse model of in vivo test, and its mechanism of action was further verified.ResultsIn vitro tests showed that compound I.-27 could effectively inhibit the proliferation, migration and invasion of TNBC cells, and induce apoptosis. Transcriptomic analysis revealed that it has a dual mechanism of action. On the one hand, it inhibits tumor angiogenesis through the ID1/TSP-1 pathway. On the other hand, it promotes apoptosis through the PI3K/AKT/FoxO1 signaling pathway. In vivo tests, the compound significantly reduced tumor volume and inhibited lung metastasis through mouse models. It further confirmed that ID1 is a key target for anti-tumor.ConclusionsIn this study, an anti-TNBC drug with multiple mechanisms was developed from the triterpenoids of 3,4-3,4-seco-lupane triterpene derivatives for the first time, and the mechanism of action was clarified by combining transcriptomics, molecular docking and gene knockout technologies. Compound I-27 provides a potential breakthrough for the treatment of triple-negative breast cancer as a potential therapeutic candidate with a novel action mechanism and high potency.